Zygonemella: the forgotten genus of the family Xyalidae (Nematoda) - Cunha, Beatriz Pereira; Brito, Simone; Fonseca, Gustavo (Zootaxa, 2013)
Species descriptions of the family Xyalidae, as well as of most marine nematodes, were in general largely made in the past century (e.g. Allgén, 1927; Cobb, 1920; Gerlach, 1957; Lorenzen, 1977). Many of these descriptions were based on one or two specimens or even on juveniles with relatively few features of taxonomic value. Lack of types and inaccuracy in sampling localities are other problems associated with taxonomy of marine nematodes. These issues, together with the fact that in the past researchers had slower exchange of information and reduced access to some journals, led to the multiplication of synonyms. To propose a new species of nematode, particularly within a genus with a convoluted historical background, requires caution and critical taxonomical review prior to the description (Adams, 2001; Fonseca & Decraemer, 2008).